0D Feature In 3D Planar Polygon Testing For 38 Spatial Analysis - Chen, Tet Khuan; Abdul Rahman, Alias (Faculty of Geoinformation Science and Engineering, 2006)
In this paper, we discuss the problem of OD feature-in-3D planar polygon. It has been recognized that 3D union and 3D intersections are among important spatial operators in 3D GIS. A 0D feature in polygon test is one of the problems in 3D GIS. Though it is a c1assic problem, however, it has not been addressed appropriately in the literature. Moreover, the 00 feature-in-polygon query is rather complicated if it is implemented into 3D spatial information system. From the aspect of 3D spatial analysis, the general 0D feature-in-3D planar polygon problem should be formulated in a suitable way. Our basic idea is to solve a general 0D feature in- 3D planar polygon problem that include all special conditions. The method addresses an essential mathematical algorithm that applicable for real objects and provides an approach for implementation in further 3D analytical operation, e.g. 3D union or 3D intersection for 3D GIS.